Radiation Dose Acceptence on Thorax Photos at Adult Patient - Dwi Rochmayanti; Darmini Darmini; Sudiyono Sudiyono (Jurnal LINK, 2014)
This study aims to describe wheter or not the patients' chest x-ray in hospital over Semarang are already has an appropriate radiation dose. This quantitative study was conducted with descriptive analysis. Data were collected by random sampling technique. The method in the measurement of patient dose was using Thermoluminesensi Dosimean meter (TLD) which is placed at the central point (CP). Profile picture over of chest radiation dose in adult patients to the 1st hospital was an average of 0.2139 mGy , 0.0758 mGy in 2nd hospital, and 0.3548 mGy in 3rd hospital . From the overall sample, the average adult chest x-ray dose was 0.1731 mGy. From these data it is concluded that the dose was still below the reference dose (0.4 mGy) , but the application of radiation protection programs and quality control diagnostic tool should still be on the run.